In silico molecular docking of quercetin as anti-colorectal cancer agents by inhibiting LT4AH - Saputra, Made Agus Widiana; Mahaswari, Anak Agung Istri Rani; Anggreni, Ni Ketut Sri; Putri, Wahyu Nadi Eka; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
Colorectal cancer is a malignant neoplasm originating from the colon or rectum. Overexpression of leukotriene A4 hydrolase (LTA4H) increases the growth of HCT116 colon cancer cells, therefore, this enzyme becomes an attractive target for commercial drug bestatin. Meanwhile, quercetin is a member of flavonoids possessing a wide variety of anticancer. This study aimed to determine the potential of quercetin as anti-colorectal cancer by inhibiting LTA4H through in silico molecular docking. The docking process involved optimizing quercetin structure, preparing LTA4H protein (PDB ID: 3U9W), validating the molecular docking method, and docking quercetin and bestatin on LTA4H. The binding energy of quercetin to LTA4H was -9.57 kcal/mol, while 28P native ligand and bestatin yielded -10.22 kcal/mol and -9.10 kcal/mol, respectively. Based on the binding energy value, quercetin has a potential inhibitory against the LTA4H.